PREFERENCES OF MILLENIAL GENERATION CUSTOMERS IN CHOOSING ISLAMIC BANKS - Chairunnisa Buay Pemaca; Egi Arvian Firmansyah (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2021)
The purpose of this study is to determine the preferences of customers in selecting Islamic Banks in Indonesia. This study uses a quantitative approach using Indonesian customers have accounts in Islamic Banks. Data were collected through a questionnaire and analyzed by Kruskal-Wallis Test Analysis. The number of respondents in this study is 200 persons. The results showed that the most preferred factor in selecting an Islamic bank is surprisingly not a religious factor. In fact, it is the comfort factors. The religious factor is in the second.